Evaluación de la gestión ambiental de la ciudad de Moyobamba - Torres Bardalez, Alfonso (2002)
The" Evaluation of the Environmental Management of the Cit y of Moyobamba", it is an research that presents information on the use of the resources related to the planning and management of the reparation and environmental control, education, urban infrastructure, socioeconomic, cultural, political aspects and ecotourists of the city; it identifies and it characterizes the agents and the more important activities that generate environmental impacts, it also identifies the environmental bid and ask of the biophysical oreas in the perspective of formulating an environmental classification and it prioritizes the resources of environmental handling to short, medium and. long term. Moyobamba is described as an urban ecosystem. and the city •ciudad de las orquídeas" is considered by its singular characteristic as for its resources paisajísticos, biodiversity (among them the 2500 species of orchids), very accepted for the receiving tourist. This is located in the district of Moyobamba, Province of Moyobamba in San Martin's Department; at the right riverbank of the río Mayo and approximately 860 meters above sea level. It's UTM coordinates are E281600 and N9332900, 2-737.5 km2 • approximately. The climate predominantly is humid, temperate and warm with rainy stations in the months of November to March; suffering variations because it suffers serious negative impacts as deforestation, migration and waste contamination. Under this scenario, the present work is justified for the lack of information that allows to see the environmental evolution pursuing a clearer horizon, with enough elements that serve like base to elaborate the development plans of the city; it also allows us to know the reality qualitatively so the government local and other institutions has an instrument to exercise his political decision in a coordinated and harmonize way under to solve the problems and to rationalize the use of the resources of the city. In a same way it contributes in the invigoration from the environmental conscience to level of authorities and population in general since, starting from the proposals they will be able to be carried out development projects and investment of short, medium and long term as for services of clean water and sewer system, handling of solid residuals, improvement of the infrastructure with projection for the tourism, equipment and urban development, rationalization of the traffic, establishment of small and medium companies among others. The investigation was developed in three stages: pre field, field, and final cabinet, inside of which were carried out the field analyses, mensurations, surveys, pesquizas, bibliographical consultations to characterize and to evaluate the variables related to biophysical aspects as physiography, hydrology, geology, climate, ecosystems and socioeconomic aspects as well as existing use of lands, socioeconomic activities, economic.growth and basic services. The results were integrated and systematized interdisciplinarty keeping in mind the global, integral and systemic nature of the environment, among those aspects that are necessary to stand out are the following: very environmental affected oreas due to the inadequate development .of the urban activities, throwing the solid residuals toward the ravines, contamination of the adjacent gulches with the city, contamination of the air for the excessive circulation of power vehicles and presence of suspended powders, sound contamination originated by the vehicles and social activities. As for the urban development, we hove as a problem the separation of the district, lawless growth of the oreas outlying, bad use of the urban lands whose constructions spread to grow horizontally, informality of the human establishments because they don't have urban qualification and they don't possess title of property, vehicular congestion when being some insufficient main streets in their carrying capacity. As for the education, culture, recreation and tourism, we have school education with out modernized libraries, lack of the population's centers educational special, scarce identity with their city, little promotion of the tourism the art and the culture local, insufficient cultural, recreational and sport infrastructure to cover the local demands. As for the economic development we hove, the informality of the mycro and small companies, trade desegregated and disperse! being developed prioritarily in activities of basic consumption, anda growing agricultura! activity that presents problems of profitability and productivity. The ansersment, includes a study of Evaluation of Environmental Impact (EEI) of the Strategic Plan for the Moyobamba city 2001-2008; in which according to the prioritized thematic axes and environmental demand; and the decisive environmental factors in the city that represent the environmental offer; it is determined the indexes and good levels of environmental quality in the study orea. In general, of the 5148 Units of Environmental Impact (UEI) defined, it has been identified 2297 impacts with valuation of 0.625 that it qualif ies like good impact under , also expressed as 62.5% of environmental quality. It allows us to visualize the strategies and methods to face the main components that become threats of the management actions and environmental development for the Moyobamba city. The technical viability and politics of the strategic plan is guaranteed under the following proposals or general considerations: Strengthening of the capacity of administration of the Municipality and base organizations. Efficient control process and territorial classification. Practica! viability of promotion for the tourism. Execution of conservation and handling plans in ravines and the environment of the city of Moyobamba. Improvement of the quality of services. Establishment of agreement spaces and intersectorial work for the development of social infrastructure and of services. Improvement and implementation of support systems to the productive sector. To strengthen the organizations of producers and to generate permanent encounters with all the agrarian sectors. To promote the installation of small and medium agroindustrial companies. Therefore, it is recommended to develop the proposals of the alternative programs; always impacting in the active participation of the public sector, prívate and the population in general, creating and strengthening environtnental conscience, agreement spaces and wide convocation based on the will and political and financia! responsibility. Key words: Environmental administration, Evaluation of environmental Impact, impacts, alternative programs, agreement, conservation, handling, promotion, units of environmental impact. resources related to the planning and management of the reparation and environmental control, education, urban infrastructure, socioeconomic, cultural, political aspects and ecotourists of the city; it identifies and it characterizes the agents and the more important activities that generate environmental impacts, it also identifies the environmental bid and ask of the biophysical oreas in the perspective of formulating an environmental classification and it prioritizes the resources of environmental handling to short, medium and. long term. Moyobamba is describedas an urban ecosystem. and the city · ciudad de las orquídeas" is considered by its singular characteristic as for its resources paisajísticos, biodiversity (among them the 2500 species of orchids), very accepted for the receiving tourist. This is located in the district of Moyobamba, Province of Moyobamba in San Martin's Department; at the right riverbank of the río Mayo and approximately 860 meters above sea level. It's UTM coordinates are E281600 and N9332900, 2-737.5 km approximately. The climate predominantly is humid, temperate and warm with rainy stations in the months of November to March; suffering variations because it suffers serious negative impacts as deforestation, migration and waste contamination. Under this scenario, the present work is justified for the lack of information that allows to see the environmental evolution pursuing a clearer horizon, with enough elements that serve like base to elaborate the development plans of the city; it also allows us to know the reality qualitatively so the government local and other institutions has an instrument to exercise his political decision in a coordinated and harmonize way under to solve the problems and to rationalize the use of the resources of the city. In a same way it contributes in the invigoration from the environmental conscience to level of authorities and population in general since, starting from the proposals they will be able to be carried out development projects and investment of short, medium and long term as for services of clean water and sewer system, handling of solid residuals, improvement of the infrastructure with projection for the tourism, equipment and urban development, rationalization of the traffic, establishment of small and medium companies among others. The investigation was developed in three stages: pre field, field, and final cabinet, inside of which were carried out the field analyses, mensurations, surveys, pesquizas, bibliographical consultations to characterize and to evaluate the variables related to biophysical aspects as physiography, hydrology, geology, climate, ecosystems and socioeconomic aspects as well as existing use of lands, socioeconomic activities, economic .growth and basic services. The results were integrated and systematized interdisciplinarty keeping in mind the global, integral and systemic nature of the environment, among those aspects that are necessary to stand out are the following: very environmental affected oreas due to the inadequate development .of the urban activities, throwing the solid residuals toward the ravines, contamination of the adjacent gulches with the city, contamination of the air for the excessive circulation of power vehicles and presence of suspended powders, sound contamination originated by the vehicles and social activities. As for the urban development, we hove as a problem the separation of the district, lawless growth of the oreas outlying, bad use of the urban lands whose constructions spread to grow horizontally, informality of the human establishments because they don't have urban qualification and they don't possess title of property, vehicular congestion when being some insufficient main streets in their carrying capacity. As for the education, culture, recreation and tourism, we have school education with out modernized libraries, lack of the population's centers educational special, scarce identity with their city, little promotion of the tourism the art and the culture local, insufficient cultural, recreational and sport infrastructure to cover the local demands. As for the economic development we hove, the informality of the mycro and small companies, trade desegregated and disperse! being developed prioritarily in activities of basic consumption, anda growing agricultura! activity that presents problems of profitability and productivity. The ansersment, includes a study of Evaluation of Environmental Impact (EEI) of the Strategic Plan for the Moyobamba city 2001-2008; in which according to the prioritized thematic axes and environmental demand; and the decisive environmental factors in the city that represent the environmental offer; it is determined the indexes and good levels of environmental quality in the study orea. In general, of the 5148 Units of Environmental Impact (UEI) defined, it has been identified 2297 impacts with valuation of 0.625 that it qualif ies like good impact under , also expressed as 62.5% of environmental quality. It allows us to visualize the strategies and methods to face the main components that become threats of the management actions and environmental development for the Moyobamba city. The technical viability and politics of the strategic plan is guaranteed under the following proposals or general considerations: Strengthening of the capacity of administration of the Municipality and base organizations. Efficient control process and territorial classification. Practica! viability of promotion for the tourism. ·XX Execution of conservation and handling plans in ravines and the environment of the city of Moyobamba. Improvement of the quality of services. Establishment of agreement spaces and intersectorial work for the development of social infrastructure and of services. Improvement and implementation of support systems to the productive sector. To strengthen the organizations of producers and to generate permanent encounters with all the agrarian sectors. To promote the installation of small and medium agroindustrial companies. Therefore,it is recommended to develop the proposals of the alternative programs; always impacting in the active participation of the public sector, private and the population in general, creating and strengthening environtnental conscience, agreement spaces and wide convocation based on the will and political and financia! responsibility. Key words: Environmental administration, Evaluation of environmental Impact, impacts, alternative programs, agreement, conservation, handling, promotion, units of environmental impact.